(untitled) (Environment & Health, 2016)
The purpose of work - to develop a classification of risks from the mother and child in the perinatal period of life. Materials and methods. Pregnant women, infants and children under 1 year of age without any diseases. Infants and children under 1 year of age with lesions of the central nervous system, which manifests itself in violation of the motor function of the child. Methods of functional diagnostics, forecasting of the body, mathematical statistics. Results. The classification confirms the need for complex interaction of medical personnel and perinatal centers neopatolohiv to detect risk factors of perinatal risk pregnancy and neonatal while determining the reasons that caused it. This approach demonstrates the need for providing modern medical equipment and systems information these centers and clinics. An obligatory element of such systems should subsystems decision support rods in order improve the accuracy and reliability of the diagnosis and the effectiveness of the selected treatment. A new promising direction reduce perinatal pathology, optimization , a real opportunity the formative personality of the child, better psycho-emotional development, Reduction ynvalydnosty with childhood is perinatal rehabilitation of the fetus and newborn. The term “rehabilitation”, which is familiar to physicians, refers to situations, in which recovery of lost functions is really required. At the same time, when Speech are talking about the development fetus and newborn, it is necessary Create all terms to implement the physiological development, and a view perinatal rehabilitation. Conclusions. For medical institutions, this means rapid flow of information to the doctor, so that he is able to timely detection and correction of risks arising in the perinatal period and can endanger the life of the child and the mother.